Splenic rupture and fungal endocarditis in a pediatric patient with invasive fusariosis after allogeneic hematopoietic stem cell transplantation for aplastic anemia: A case report - Hannemann, Maurice; Wilmes, Dunja; Dombrowski, Frank; Löffler, Jürgen; Kaminski, Alexander; Hummel, Astrid; Ulm, Lena; Bohnert, Jürgen; Rickerts, Volker; Springer, Jan; Lode, Holger N.; Ehlert, Karoline (Frontiers in Pediatrics, 2022)
Background Invasive mold infections are a well-known and life-threatening condition after allogeneic hematopoietic stem cell transplantation (HSCT). While Aspergillus species are recognized as predominant pathogens, Fusarium species should also be considered due to their broad environmental distribution and the expected poor outcome of invasive fusariosis. Particularly, splenic rupture as a complication of disseminated disease has not been reported yet. Case presentation Two weeks after allogeneic HSCT for severe aplastic anemia, a 16-year-old boy presented with painful, erythematous skin nodules affecting the entire integument. As disseminated mycosis was considered, treatment with liposomal amphotericin B and voriconazole (VCZ) was initiated. Invasive fusariosis was diagnosed after histological and previously unpublished polymerase chain reaction-based examination of skin biopsies. Microbiological tests revealed Fusarium solani species. Despite stable neutrophil engraftment and uninterrupted treatment with VCZ, he developed mold disease-associated splenic rupture with hypovolemic shock and fungal endocarditis. The latter induced a cardiac thrombus and subsequent embolic cerebral infarctions with unilateral hemiparesis. Following cardiac surgery, the patient did not regain consciousness because of diffuse cerebral ischemia, and he died on day +92 after HSCT. Conclusion Invasive fusariosis in immunocompromised patients is a life-threatening condition. Despite antimycotic treatment adapted to antifungal susceptibility testing, the patient reported here developed uncommon manifestations such as splenic rupture and fungal endocarditis.